Analysis of Student’s Mathematical Reasoning in terms of Learning Independence During Distance Learning - Nuzula Erlisa Nuraziza; Susanto Susanto; Abi Suwito; Dinawati Trapsilasiwi; Reza Ambarwati (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2022)
Mathematical reasoning is the student’s ability to think logically regarding mathematics problems. The indicators of mathematical reasoning used in this study are presenting statements mathematically, performing mathematical manipulations, compiling the proofs for the truth of solutions, and drawing conclusions from statements presented. This study used qualitative research methods and aims to describe the students' mathematical reasoning abilities for the subject of Three Dimensions, reviewed by their learning independence during Distance Learning. This research was conducted at SMAN 1 Pasuruan class XII MIPA 1 for the 2021/2022 academic year. The instruments used in this study are learning independence questionnaires, mathematical reasoning ability tests, and guides for the interview. The results showed that 21 students can be categorized into Medium Level in terms of their learning independence, and 14 students can be categorized into High Level in terms of their learning independence. Students who have medium learning independence showed medium and low mathematical reasoning abilities. Students are able to solve problems by fulfilling two indicators of mathematical reasoning ability. On the other hand, students with high learning independence showed high mathematical reasoning abilities. Students are able to solve problems by fulfilling all indicators of mathematical reasoning abilities.